Optimizing the Use of Oce-Card Media as a Learning Tool for Local Wisdom of the Osing Kemiren Tribe at MAN 2 Banyuwangi - Arifah, Kiki Ayu; Al Atok, A. Rosyid; Awaliyah, Siti (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to determine the optimization of the use of oce-card media as a means of learning local wisdom of the Osing Kemiren tribe at MAN 2 Banyuwangi. The method used in this study uses a 4D model approach consisting of four stages: define, design, develop, and disseminate. Data collection techniques include validation questionnaires, pretest results, and posttests, while data analysis is carried out descriptively through three stages: analysis of validation results by experts, analysis of attractiveness tests, and analysis of effectiveness. The results of the study show that the Oce Card media Oce-Card media as a technology and culture-based learning innovation plays a role in increasing students' understanding of local wisdom and strengthening national identity. Combining augmented reality technology and an interactive approach, this media makes learning more interesting and encourages exploration of the Osing Kemiren Tribe culture. The implications are seen in increasing cognitive understanding, forming a sense of pride in local culture, and supporting constructivist learning models.